2019
DOI: 10.1259/bjr.20181055
|View full text |Cite
|
Sign up to set email alerts
|

MRI evaluation of extramural vascular invasion by inexperienced radiologists

Abstract: Objective: We proposed to determine whether the performance of inexperienced radiologists in determining extramural vascular invasion (EMVI) in rectal cancer on MRI can be promoted by means of targeted training. Methods: 230 rectal cancer patients who underwent pre-operative chemoradiotherapy were included. Pre-therapy and post-therapy MR images and pathology EMVI evaluation were available for cases. 230 cases were randomly divided into 150 training cases and 80 testing cases, including 40 testing case A and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…A study examining the accuracy of screening mammogram interpretation found that radiologists who followed up cases in which they recommended further workup had higher specificity, while the interpretation of a higher volume of mammograms was not associated with better performance [28] . Similarly, diagnosis of extramural venous invasion in rectal cancer improved significantly following targeted training which included histological correlation, while there was no improvement in diagnostic accuracy for radiologists who performed clinical work without the targeted training [29] .…”
Section: Discussionmentioning
confidence: 99%
“…A study examining the accuracy of screening mammogram interpretation found that radiologists who followed up cases in which they recommended further workup had higher specificity, while the interpretation of a higher volume of mammograms was not associated with better performance [28] . Similarly, diagnosis of extramural venous invasion in rectal cancer improved significantly following targeted training which included histological correlation, while there was no improvement in diagnostic accuracy for radiologists who performed clinical work without the targeted training [29] .…”
Section: Discussionmentioning
confidence: 99%
“…MREMVI is a promising prognostic factor in rectal cancer, but can be difficult to assess. Two of the four inexperienced radiologists in a study by Wang et al received targeted training resulting in a 20% increase in agreement with expert reference [18]. A computer‐based self‐training module also showed improvement in lesion sensitivity on CT colonography from 74% to 83% ( p < 0.001) [22].…”
Section: Discussionmentioning
confidence: 99%
“…The training improved the overall agreement with the expert reference (53% before and 70% after the training). Radiological training for a higher agreement with the expert reference has previously been described to be of added value for the detection of extramural venous invasion on MRI (MREMVI) and the assessment of CT colonography [18][19][20][21]. MREMVI is a promising prognostic factor in rectal cancer, but can be difficult to assess.…”
Section: F I G U R Ementioning
confidence: 99%
“…All the patients underwent total mesorectal excision, which was confirmed by pathology after operation. According to the definition of EMVI in pathology ( 8 ), the positive criteria for EMVI were as follows: tumor cells were observed by HE staining to encase and invade the adipose tissue around the intestinal wall or the vascular wall under the serous membrane, or tumor cells invaded the vascular lumen outside the intestinal wall to form tumor cell emboli.…”
Section: Methodsmentioning
confidence: 99%